How the Organizational Goals Affect Knowledge Management - Wei-Shong Lin; Jui-Ling Huang; Margaret L. Sheng (International School for Social and Business Studies, 2014)
How to enhance customer satisfaction and technology innovation have been topics of discussion for some time; however, few studies have explored the two issues by applying the knowledge creation theory, and analyzed their differences in knowledge creation activities. The present study aims to explore how the firm's organizational goal affects its knowledge creation process. Based on Nonaka's knowledge creation theory, questionnaires were developed and sent to Taiwanese firms in various industries, including the manufacturing and service industries. These questionnaires were collected either by mail or interview. Our findings suggest that externalization and combination activities should be emphasized when the organizational goal is innovation, whereas internalization activity should be emphasized when the organizational goal is customer satisfaction.